Neuropsychological impairment in children following head injury - Hemp, Frances (Division of Neurosurgery, 2017)
There is a high incidence of head injury in children, yet few studies have systematically studied cognitive outcome. This study was designed as a survey to (a) establish the nature of intellectual and neuropsychological deficits that occur after head injuries of differing severity in children aged 6 to 14 years, (b) establish the nature of recovery curves in the first year after injury, and (c) determine which medical and psychosocial factors are associated with poor cognitive outcome and which functions show persisting impairment. From 1134 children admitted with head injury to Red Cross and Groote Schuur Hospitals during a 2-year period, a consecutive sample of all those who had post-traumatic amnesia (PTA) over 1 hour, a compound depressed or basal skull fracture, a seizure, or any evidence of neurological involvement, was collected (n=388). Further requirements that they should be between 6 and 14 years, English or Afrikaans speaking, and have no history of significant cerebral pathology or mental retardation, reduced the sample to 123 children. Severity groups were formed according to the length of PTA: 56 moderates (PTA less than 1 day), 40 severes (PTA 1 to 7 days), and 28 very severes (PTA more than 7 days). They were matched for age, sex, socioeconomic status and ethnic group with 46 controls who had traumatic injury not involving the head. Detailed accident, medical and psychosocial data were collected. The children were assessed on a battery of tests covering intelligence, language, motor speed, visuographic and memory functions, as soon as they were out of PTA (Tl), 3 months later (T2), and at 1-year post-injury (T3). The 4 groups are compared at each interval on Tukey' s studentized range test and the extent of recovery within and between the groups is compared by repeated measures analysis of variance.